PENGEMBANGAN GREEN INNOVATION PLATFORM SDGs PADA PELAKU UMKM DI INDONESIA - Rohmawan Adi Pratama (Universitas Sarjanawiyata Tamansiswa, 2023)
Sustainable Development Goals (SDGs) apply universally so that all countries in the world take part in supporting the goals of the SDGs, including Indonesia. SDGs are designed by involving all development starting from the government, Civil Society Organizations, private sector, youth, and so on, behind in taking the role is SMEs in Indonesia. SMEs are the most significant part of the economy in Indonesia. Many SMEs who don’t understand how to continue to grow and expand their business. Especially in the industrial era 4.0, where use of technology is an absolute must for SMEs to develop. Good and correct marketing and financial management also things that need to be implemented in order to maximize the profits obtained. Objects in this study are SMEs actors in Indonesia, with a total sample of 163 respondents. This research is an empirical interpretive designed with a quantitative approach. In the process of testing the hypothesis, used PLS-SEM. Results show that the variables of green marketing orientation, government regulation, and human resource management have a significant positive on the green innovation platform SDGs for SMEs in Indonesia. Government regulation mediates green marketing orientation, digital technology, and human resource management on the green innovation platform SDGs for SMEs in Indonesia. This research is expected to be a foothold for all policy makers on the importance of understanding green innovation as a matching indicator to increase equitable economic growth through green innovation that can encourage SDGs in SMEs, especially programs to overcome environmental damage.